Ethics In Business Communication: Building Trust and Corporate Reputation - Innek Safitri; Havis Aravik (CV. Picmotiv, 2025)
Business communication is one of the major challenges of the world of work, including in the business sector. The implementation of ethics in business communication based on the ethical principles of fairness, transparency, and social responsibility can act as an effective mechanism for building trust and corporate reputation. This research aims to examine ethics in communication to build trust and reputation of the company. The method used is descriptive qualitative analysis which aims to describe or describe the existing reality or what happens or the actual reality in the object under study through qualitative studies. The results of this study indicate that ethics in communication is very influential on the company's reputation and honesty if good communication is proven to make a significant contribution in creating a transparent work environment and preventing fraudulent practices. In addition, commitment to communication ethics and building strict trust are also important in reducing the potential for corporate reputation. This research provides recommendations to strengthen the implementation of integrity-based work culture business ethics in the business world.